Qualitative characteristics of meat from confined crossbred heifers fed with lipid sources - Fiorentini, Giovani [UNESP]; Berchielli, Telma Teresinha [UNESP]; Santana, Márcia Cristina Araújo [UNESP]; Dian, Paulo Henrique Moura [UNESP]; Reis, Ricardo Andrade [UNESP]; Sampaio, Alexandre Amstalden Moraes [UNESP]; Biehl, Marcos Vinicius (FapUNIFESP (SciELO), 2012)
Lipids have been used in ruminant feed to replace high amounts of grain for increasing the diet energy density, performance and meat quality. This study evaluated the qualitative characteristics of meat from feedlot heifers fed with sources of lipid supplements. Twenty-one crossbred heifers (1/4Nelore × 1/4Santa Gertrudis × 1/2Braunvieh) were used. Each heifer received 60 % forage with a base of corn silage and 40 % concentrate, resulting in 5.8 % lipid content in the total diet. The following sources of lipids were used: soybeans, protected fat and soybean oil. There were no differences on physical characteristics of meat samples from heifers fed with the lipid sources. Soybeans increased the concentration of linoleic acid, content of polyunsaturated fatty acid and activity of the Δ9-desaturase C16 enzyme in the Longissimus muscle. The use of soybean oil in the diet increased the oleic acid, monounsaturated fatty acid, total cis- and trans-fatty acids (C18:0) and the activity of the Δ 9-desaturase C16 enzyme in the subcutaneous fat. Diets with soybean grain had greater deposition of linoleic and linolenic acids than diets with fat protected and greater presence of these essential fatty acids are associated to a better composition and meat quality.
Keywords: Meat quality; Protected fats; Soybean oil; Soybeans